2021
DOI: 10.1016/j.clnu.2020.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D 25OH deficiency in COVID-19 patients admitted to a tertiary referral hospital

Abstract: Background & Aims Great interest has been raised by the possible protective role of vitamin D in coronavirus disease 2019 (COVID-19), but objective data on 25(OH)vitamin D deficiency in hospitalized COVID-19 patients are not conclusive. The aim of this study was to determine the prevalence of 25(OH)vitamin D deficiency in COVID-19 patients admitted to an Italian referral hospital and explore its association with clinical outcomes and the markers of disease severity. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 10 publications
1
84
1
11
Order By: Relevance
“…Among 15 studies that assessed the relation between mortality and VDD, 13 studies were included in the analysis. Pooled analysis of 4 adjusted studies that used the Cox survival method ( 13 , 51 , 56 , 60 ) (HR: 2.35; 95% CI: 1.22, 4.52; I 2 : 84%; Figure 4 A ) and 5 studies ( 44 , 47 , 53 , 55 , 62 ) with crude OR (OR: 2.62; 95% CI: 1.13, 6.05; I 2 : 47.8%; Figure 4B ) indicated a significant association of VDD with mortality, while in adjusted studies that used logistic regression ( 54 , 59 , 65 ), no relation was observed (OR: 1.05; 95% CI: 0.63, 1.75; I 2 : 76.6%). Two studies were not included in the analysis since 1 study had an RCT design ( 36 ) and another one used different statistical methods ( 64 ).…”
Section: Resultsmentioning
confidence: 97%
“…Among 15 studies that assessed the relation between mortality and VDD, 13 studies were included in the analysis. Pooled analysis of 4 adjusted studies that used the Cox survival method ( 13 , 51 , 56 , 60 ) (HR: 2.35; 95% CI: 1.22, 4.52; I 2 : 84%; Figure 4 A ) and 5 studies ( 44 , 47 , 53 , 55 , 62 ) with crude OR (OR: 2.62; 95% CI: 1.13, 6.05; I 2 : 47.8%; Figure 4B ) indicated a significant association of VDD with mortality, while in adjusted studies that used logistic regression ( 54 , 59 , 65 ), no relation was observed (OR: 1.05; 95% CI: 0.63, 1.75; I 2 : 76.6%). Two studies were not included in the analysis since 1 study had an RCT design ( 36 ) and another one used different statistical methods ( 64 ).…”
Section: Resultsmentioning
confidence: 97%
“…Table A describes the characteristics of the 31 included observational studies ordered by outcome severity [ [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ]. These studies reported on mortality from COVID-19 ( n = 20), ICU admission ( n = 5), length of ICU stay ( n = 1), invasive ventilation ( n = 7), non-invasive ventilation ( n = 4), hospitalization ( n = 3), length of hospital stay (n = 5), disease severity ( n = 12), pneumonia (n = 1), multi-organ damage (n = 1), acute kidney injury (n = 1), ARDS (n = 5), SARS-CoV-2 positivity (n = 4), and 25(OH)D levels ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
“…A clinically relevant issue is to understand whether hypovitaminosis D may influence the outcome of COVID-19 [12]. Some studies provided evidence that subjects exposed to vitamin D deficiency may develop a more severe COVID-19 [13][14][15][16], whereas other studies failed to find such an association [17][18][19]. Moreover, the effects of vitamin D supplementation on clinical outcome of COVID-19 is still a matter of uncertainty [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Variability in clinical end-points may explain the heterogeneity of results of these studies evaluating the impact of hypovitaminosis D and its treatment on COVID-19 outcome. Moreover, the potential effects of low calcium [23][24][25] and high parathyroid hormone (PTH) [17,25] may influence the impact of hypovitaminosis D on the outcome of COVID-19.…”
Section: Introductionmentioning
confidence: 99%